2018
DOI: 10.1039/c8cp04193h
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics of OH + HNO3 under conditions relevant to the upper troposphere/lower stratosphere

Abstract: The OH initiated oxidation of HNO3 in the UT/LS plays an important role in controlling the O3 budget, removing HOx radicals whilst driving NOx/y partitioning chemistry by yielding NO3 radicals: OH + HNO3 → H2O + NO3. In this paper, k1(T, P) was measured using OH (A ← X) Laser Induced Fluorescence (LIF) and the data was modelled over the 223-298 K temperature and 25-750 Torr pressure ranges, using the modified Lindemann-Hinshelwood expression , where k0 = 5.2 × 10-14 exp(200/T) cm3 s-1, k2 = 8.4 × 10-17 exp(190… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…⟨ ΔE ⟩ d is varied from 50 to 175 cm –1 with a step size of 25 cm –1 . As seen in Figure , all calculated k ( T , P ) are in good agreement (within 20%) with the experimental results. Theory with ⟨ ΔE ⟩ d = 50 cm –1 agrees with the experiment of Dulitz et al, while a higher value of ⟨ ΔE ⟩ d = 175 cm –1 is desirable to match the experimental results of Brown et al The overall best fit between theory and experiment in this scenario is found with ⟨ ΔE ⟩ d ∼ 100 cm –1 . Following the same strategy, we did the same at other temperatures (from 210 to 350 K), where experimental data are available, and a good agreement between theory and experiment has been seen (see Figure S1 in the Supporting Information).…”
supporting
confidence: 75%
See 4 more Smart Citations
“…⟨ ΔE ⟩ d is varied from 50 to 175 cm –1 with a step size of 25 cm –1 . As seen in Figure , all calculated k ( T , P ) are in good agreement (within 20%) with the experimental results. Theory with ⟨ ΔE ⟩ d = 50 cm –1 agrees with the experiment of Dulitz et al, while a higher value of ⟨ ΔE ⟩ d = 175 cm –1 is desirable to match the experimental results of Brown et al The overall best fit between theory and experiment in this scenario is found with ⟨ ΔE ⟩ d ∼ 100 cm –1 . Following the same strategy, we did the same at other temperatures (from 210 to 350 K), where experimental data are available, and a good agreement between theory and experiment has been seen (see Figure S1 in the Supporting Information).…”
supporting
confidence: 75%
“…The purpose of this work is to examine the largely unexplored pressure dependence of κ­( T ) and to check whether there is a connection between quantum mechanical tunneling and the falloff curve. The reaction of OH and HNO 3 , which significantly affects stratospheric ozone, the HO x budget, as well as NO x partitioning in the upper troposphere and lower stratosphere (UTLS), is chosen as an example because this bimolecular reaction (which also displays a pressure dependence) has been well-characterized experimentally. …”
mentioning
confidence: 99%
See 3 more Smart Citations